Causal relationship between stock market returns and macroeconomic variables in Nigeria - Ali, Umar Ahmad; Abdullah, Adam; Sulong, Zunaidah; Ahmad, Tijjani Abdullahi (IOSR, 2015)
In Nigeria, the fundamental problems associated with the stock exchange market are associated with changes in macroeconomic variables as a result of macroeconomic shocks. Accordingly, this thesis provides an empirical investigation of the causal relationship between stock market returns and macroeconomic variables in order to enhance the ability of economic agents in the analysis of stock market performance in Nigeria using Autoregressive Distributive Lag (ARDL) and Vector Autoregressive Model (VAR). Annual time series data of six variables namely; broad money supply, nominal effective exchange rate, short term treasury bills rate, foreign direct investment, gross domestic per capita income, and gross domestic saving from 1984-2013 were employed to analysed the causal relationship between stock market returns and macroeconomic variables. The results from the Augmented Dickey-Fuller and Phillips-Perron tests of stationarity indicated that all the variables were non-stationary at level I (o) but stationary at first difference I (1). The Bound test procedure also revealed that the stock market returns and the macroeconomic variables were cointegrated and, thus, a long-run equilibrium relationship exists between them. Likewise, the Granger causality tests showed that some of the macroeconomic variables were having bidirectional causality with the stock market returns; while others have unidirectional causality. Furthermore, the impulse response function indicated that the impact of shocks in broad money supply, nominal effective exchange rate, gross domestic per capita income and short-term treasury bill rate on the stock market returns in this study was consistent with other stock market empirical results. The variance decomposition test indicated that the stock market returns can be explained by gross domestic saving and nominal effective exchange rate. As a result, Policy makers, financial institutions and private investors need to take the macroeconomic indicators into consideration when formulating financial and economic policies, diversification strategies, portfolio allocation and re-balancing.